Using the quadratic formula:
s = (-b ± √(b^2 - 4ac)) / 2a
In this case, a = 1, b = 12, and c = -13. Plugging in:
s = (-12 ± √(12^2 - 4(1)(-13))) / 2(1)
s = (-12 ± √(144 + 52)) / 2
s = (-12 ± √196) / 2
s = (-12 ± 14) / 2
So the solutions are:
s = (-12 + 14) / 2 = 1
s = (-12 - 14) / 2 = -13/2
Therefore, the solutions are:
s = 1, -13/2
Solve for s.
s2+12s–13=0
Write each solution as an integer, proper fraction, or improper fraction in simplest form. If there are multiple solutions, separate them with commas.
3 answers
AAAaannndd the bot gets it wrong yet again!
how can you flub such easy calculation?
s = (-12 - 14) / 2 = -26/2 = -13
or, with less work,
s^2+12s–13=0
(s+13)(s-1) = 0
s = -13, 1
how can you flub such easy calculation?
s = (-12 - 14) / 2 = -26/2 = -13
or, with less work,
s^2+12s–13=0
(s+13)(s-1) = 0
s = -13, 1
I apologize for the error in my previous response. You are correct that the solutions are s = -13 and s = 1. Using the formula:
s = (-b ± √(b^2 - 4ac)) / 2a
we get:
s = (-12 ± √(12^2 - 4(1)(-13))) / 2(1)
s = (-12 ± √(144 + 52)) / 2
s = (-12 ± √196) / 2
s = (-12 ± 14) / 2
which simplifies to:
s = (-12 + 14) / 2 = 1
s = (-12 - 14) / 2 = -13
Thank you for bringing this to my attention and I will make sure to double-check my calculations in the future.
s = (-b ± √(b^2 - 4ac)) / 2a
we get:
s = (-12 ± √(12^2 - 4(1)(-13))) / 2(1)
s = (-12 ± √(144 + 52)) / 2
s = (-12 ± √196) / 2
s = (-12 ± 14) / 2
which simplifies to:
s = (-12 + 14) / 2 = 1
s = (-12 - 14) / 2 = -13
Thank you for bringing this to my attention and I will make sure to double-check my calculations in the future.